2022
DOI: 10.3390/bioengineering9100569
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Habit on Peri-Implant Indicators following Different Therapies: A Systematic Review

Abstract: Peri-implant disease and its treatment is becoming a major concern for clinicians as the number of implants placed each year is rising. Smoking is a common habit, and it is associated with an increased risk of developing peri-implant disease. The role of smoking in the response to peri-implant treatment has never been investigated. Searches were conducted in electronic databases to screen articles published until August 2021. The included studies had at least two groups of patients: peri-implant disease only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…On the other hand, in a study evaluating the phenomenon of corticalization of the peri-implant jawbone in tobacco smokers, a correlation was observed between smoking and changes in bone structure in radio textures near the implants [ 10 ]. Other studies have shown that smoking may affect the outcome of peri-implant disease treatment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a study evaluating the phenomenon of corticalization of the peri-implant jawbone in tobacco smokers, a correlation was observed between smoking and changes in bone structure in radio textures near the implants [ 10 ]. Other studies have shown that smoking may affect the outcome of peri-implant disease treatment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent literature, a key role for the onset and progression of peri-implantitis can be ascribed to the oxidative stress due to diabetes mellitus [6] and other unfavorable local and systemic metabolic conditions causing an inflammatory burden [7], in association with a polymicrobial infection that may affect peri-implant bone and soft tissues [8]. Also, like periodontitis, a greater risk of developing peri-implantitis as well as worse outcomes of both surgical and nonsurgical treatment have been observed in tobacco smokers, as compared to non-smokers [9]. A recent comparative study demonstrated that smoking cigarettes may adversely affect the primary and secondary stability of implants immediately placed in post-extraction sockets [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-related factors peri-implantitis include smoking, systemic diseases, osteoporosis, long-term corticosteroid treatment, chemotherapy [29][30][31][32]. Patients with type 2 diabetes are at high risk of peri-implantitis [33].…”
Section: Introductionmentioning
confidence: 99%